2020
DOI: 10.18502/ijm.v11i6.2223
|View full text |Cite
|
Sign up to set email alerts
|

The potency of luliconazole against clinical and environmental Aspergillus nigri complex

Abstract: Background and Objectives: Black Aspergillus strains including, Aspergillus niger and A. tubingensis, are the most cause of otomycosis with worldwide distribution. Although, amphotericin B was a Gold standard for the treatment of invasive fungal infection for several decades, it gradually replaced by fluconazole and /or voriconazole. Moreover, luliconazole, appears to offer the best potential for in vitro activity against black Aspergillus strains. The aim of the present study was to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Species of Aspergillus section Nigri were reported as the most frequently isolated pathogens from otomycosis, but they are less commonly found in clinical samples ( 26 ). In the present study, the lowest MIC GM values observed in Aspergillus section Nigri were for LUL, CAS, and ISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Aspergillus section Nigri were reported as the most frequently isolated pathogens from otomycosis, but they are less commonly found in clinical samples ( 26 ). In the present study, the lowest MIC GM values observed in Aspergillus section Nigri were for LUL, CAS, and ISA.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the lowest MIC GM values observed in Aspergillus section Nigri were for LUL, CAS, and ISA. According to the work of Hivary et al, the lowest MIC range, MIC 90 , and MIC GM values for species of Aspergillus section Nigri in Iran belonged to LUL, and 86.7% of clinical isolates were sensitive to VOR ( 26 ). Moreover, 86.5%, 54.1%, and 83.8% of isolates in the work of Hivary et al were found to be resistant to AMB, CAS, and POS, respectively ( 26 ), and these data are similar to those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Luliconazole is an FDA-approved imidazole antifungal agent that is typically administered in a topical cream, and primarily prescribed for the fungal foot infection, tinea pedis [59]. Currently, luliconazole is being investigated for its use against a broad spectrum of fungal afflictions including aspergillosis, dermatophytosis, and onychomycosis [60]. Ravuconazole is a triazole antifungal approved for clinical use in Japan for treatment of tinea pedis but has yet to receive FDA approval [61].…”
Section: Discussionmentioning
confidence: 99%
“…Luliconazole was recently shown a potent in vitro activity against Aspergillus species including A. fumigatus (2), A. terreus (5), A. flavus (7) and A. niger complex (34) in comparison with other routine antifungal drugs. However, there is no data about the efficacy of luliconazole on A. flavus with otomycosis sources.…”
Section: Discussionmentioning
confidence: 99%